TURIZMNING TASHKILIY SHAKLLARI VA ASOSIY KATEGORIYALARI - Axmadaliev Bexruz (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article will study the organizational forms and main categories of Tourism. Literature analysis and empirical data studies have been used as research methods. The article analyzes the main organizational forms of Tourism – International, Domestic, incoming and outgoing tourism, highlighting their distinctive features and significance. Also, the main categories of tourism – recreation, cultural-historical, sports, environmental, business and other types of tourism-are studied in detail. The results of the study show that each organizational form and category of tourism has its own opportunities and problems. The conclusions from this study are of practical importance for the further development and improvement of the tourism sector.